Fleksibilitas dan Kesederhanaan Arsitektur Sistem Operasi Linux - Hilman Ihza Amrullah; Alif Nur Fathlii Amarta; Elkin Rilvani (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This research describes the flexibility and simplicity of the Linux operating system architecture. These are the main factors behind its popularity in various technological applications. This study uses a literature approach to explore kernel modularity, extensive file system support, and kernel modularity in meeting the needs of users in various computing environments, ranging from the Internet of Things (IoT) to large-scale servers. Research shows that the modular structure of Linux makes it easy to customize the operating system without compromising stability. In addition, the open source nature of Linux supports learning and innovation among the global community. Despite the challenges of development complexity, the open source community remains committed to providing documentation and tools to support the user experience. With flexibility and simplicity at the core of its design, Linux continues to adapt to the rapid advancement of information technology.